Yield and Seed Quality of Wheat as Affected by Seeding Dates and Boron Levels at Rampur, Chitwan - Chhetri, Bishwo B.; Sah, Shrawan K.; Marahatta, Santosh; Parajuli, Tulsi (Agronomy Journal of Nepal, 2023)
Yield and seed quality of wheat is affected by sowing dates through its impacts on growing environment, soil moisture content and terminal heat stress. Boron fertilization also impacts on number of seed per spike and quality of the seed. A field experiment was laid out in split-plot design with four sowing dates (15 November, 30 November, 15 December and 30 December) in main plot and four boron levels (0, 1, 2 and 3 kg ha-1) on sub-plot, replicated thrice to assess the effect of sowing dates and boron levels on yield and seed quality of wheat at Rampur, Chitwan during winter season of 2019. The results revealed that significantly highest grain yield was obtained on November sown wheat compared to December sowing. Highest grain yield was obtained with the application of boron at 3 kg ha-1, significantly higher than 0 and 1 kg ha-1 boron application. Significant interaction among sowing dates and boron levels was found on grain and seed yield. Seed quality parameters viz; seedling root and shoot length, vigour indices I and II were better in the earlier sown wheat and with 3 kg ha-1 boron application. The germination was also higher in earlier sown wheat but not affected by boron levels. Therefore, wheat with high seed quality can be sown from 15 to 30 November with 3 kg ha-1boron application in Chitwan and under similar environments.